Studies in Australian Mantodea: New synonyms, notes on distributions, and an updated checklist - Connors, Matthew G. (Zootaxa, 2023)
Despite recent advances in Mantodean systematics that have resolved many historical problems within the order, the Australian fauna still contains many erroneously recorded or incorrectly placed species. An investigation of these problematic species and related taxa necessitated a number of taxonomic changes: Exparoxypilus Beier is a new synonym of Paraoxypilus Saussure, Paraoxypilus verrauxii Wood-Mason and Exparoxypilus africanus Beier are new synonyms of Paraoxypilus verreauxii Saussure, Pthersigena Hinton is a new synonym of Phthersigena Stål, Austromantis alboterminata Sjöstedt is a new synonym of Austromantis albomarginata Sjöstedt, Deiphobe australiana Giglio-Tos is a new synonym of Coenomantis kraussiana Saussure, Notomantis Tindale is a new synonym of Pseudomantis Saussure, Hierodula dimorpha Werner is a new synonym of Pseudomantis albofimbriata (Stål), Notomantis chlorophana Tindale is a new synonym of Pseudomantis hartmeyeri Werner, Pseudomantis papua (Werner) comb. nov. is transferred from Hierodula, Orthodera marginata (Saussure) is reinstated as a valid species, and Ciulfina liturgusa Giglio-Tos and Orthodera gunnii Le Guillou are considered nomina dubia. In addition, notes are provided on the nomenclature, systematics, distribution, and ecology of several other Australian taxa, and a synonymic checklist of Australian Mantodea is provided. Finally, the origins and diversification of the Australian fauna are discussed in light of these and other recent changes.